2009
DOI: 10.1111/j.1479-8425.2008.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed waist actigraphy and its sleep/wake scoring algorithm

Abstract: The purpose of this study was to formulate an algorithm for assessing sleep/waking from activity intensities measured with a waist-worn actigraphy, the Lifecorder PLUS (LC; Suzuken Co. Ltd., Nagoya, Japan), and to test the validity of the algorithm. The study consisted of 31 healthy subjects (M/F = 20/11, mean age 31.7 years) who underwent one night of simultaneous measurement of activity intensity by LC and polysomnography (PSG). A sleep(S)/wake(W) scoring algorithm based on a linear model was determined thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 17 publications
2
54
2
Order By: Relevance
“…A sleep scoring algorithm from a different waist‐worn actigraph has recently been developed from the simultaneous measure of polysomnography and actigraphy in 31 healthy adults 21 . The authors found sensitivity, specificity and accuracy of 89.4, 58.2 and 86.9%, which is comparable to what has been seen with wrist as the attachment site in other studies 13,14,16 .…”
Section: Discussionmentioning
confidence: 69%
“…A sleep scoring algorithm from a different waist‐worn actigraph has recently been developed from the simultaneous measure of polysomnography and actigraphy in 31 healthy adults 21 . The authors found sensitivity, specificity and accuracy of 89.4, 58.2 and 86.9%, which is comparable to what has been seen with wrist as the attachment site in other studies 13,14,16 .…”
Section: Discussionmentioning
confidence: 69%
“…The details of the actigraphy procedure were described in previous studies [17,18]. Briefly, a waist-worn actigraph (FS-750; Estera Corporation, Saitama, Japan) was used to record sleep parameters.…”
Section: Methodsmentioning
confidence: 99%
“…An algorithm for the FS-750 actigraph that determines sleep and wakefulness was included in the SleepSignAct software (Kissei Comtec Co. Ltd., Matsumoto, Japan); the formula used and validation of the process for use in polysomnography (PSG) has been described in previous studies [17,18]. According to this algorithm, total sleep time was calculated as the amount of total time in bed after subtraction of the periods of wakefulness.…”
Section: Methodsmentioning
confidence: 99%
“…For these purposes, inexpensive waist actigraphy (Enomoto et al, 2009) that can score sleep/wake from waist activity and a wireless transdermal photoelectric pulse wave sensor (Takahara et al, 2008) for autonomic activity during sleep were recently developed. However, both sensors must be worn, resulting in the same drawbacks as Act.…”
Section: Discussionmentioning
confidence: 99%